2D transient parametric and heat transfer analysis of a coupled vane compressor - Koh, Daniel Han Wen (Nanyang Technological University, 2021)
With global warming becoming a major issue, having an air conditioning system will soon be a necessity. Hence there is a need to develop a refrigeration system with better energy efficiency. In this project, efforts have been made to improve the design and energy efficiency of a compressor using Computational Fluid Dynamic (CFD) analysis to further understand the operational principles of a newly introduced compressor, the Coupled Vane Compressor (CVC). CVC was designed to reduce the high rotor to cylinder volume which maximize volumetric capacity and reduces the overall physical dimension as compared to other rotary compressors. A review of existing rotary compressors was discussed. To analyse the effects of varying operational conditions, a parametric study was conducted. A study of the pressure ratio, gas velocity, possible reverse flow, temperature, density and pressure in the working chamber was conducted. Using the data from the CFD to calculate the performance and efficiency of the CVC at various speeds. Another study with in-chamber heat transfer analysis was also conducted. A comparison on the effects of compressor performance with and without heat transfer was also conducted. From the parametric study, it was noted that internal leakages are unavoidable. All simulations conducted shows backflow occurred at the suction and discharge regions. Hence, a non-return valve was added which improve the suction chamber mass flow rate. Finally, recommendation for future works is discussed to improve on the CVC which has the potential to be one of the most compact compressors in terms of cost saving.